FEATURES OF INDICATORS FOR ASSESSING THE ECONOMIC SECURITY OF THE IT SECTOR IN TIMES OF WAR - BLYNKOV, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the factors of influence and features of indicators for assessing the economic security of the IT sector in the current conditions with the introduction of the proposed separate indicator as part of the categorical matrix of economic security of the IT sector - military security. Russia's aggression has led to a serious decline in the Ukrainian economy, as the risk of security threats has reached an all-time high, with the IT sector being no exception. The purpose of the study is to analyze the current factors influencing the economic security of the IT sector and to develop a scientific and practical approach to assessing the functional components - indicators of economic security assessment, which form a categorical matrix for assessing economic security. The study, taking into account the statistical analytics of IT specialists, developed indicators within the categories, taking into account military security, influence factors, indicators of influence factors, security measures and their examples, which should be included in the categorical matrix to assess the level of sustainability and economic security of the IT industry. To assess the level of economic security by effective aspects, we use the concept of a categorical matrix. First, we define key indicators that reflect different aspects of economic security. The evaluation of such a matrix can be carried out by the "expert assessment method", which involves the involvement of experts from the relevant sector to assess the level of economic security according to certain indicators. Such an approach will allow determining the overall level of economic security and identifying the strengths and weaknesses of the IT sector economy in wartime. It is determined that the strategic guidelines of the State regulatory policy for the development of the IT sector and its economic security should be the following steps: creation of a favorable investment climate; formation of an effective policy aimed at developing a regulatory framework adequate to the requirements of wartime and strengthening the competitiveness of the sector; adaptation of the training sector to the latest demand.
Keywords: economic security of the IT sector; factors of influence; category matrix; wartime crisis